Congenital aflatoxicosis, mal-detoxification genomics & ontogeny trigger immune-mediated Kotb disease biliary atresia variant: SANRA compliant review. Issue 39 (30th September 2022) - Kotb, Magd A.; Kotb, Ahmed; Talaat, Sahar; Shehata, Sherif M.; El Dessouki, Nabil; ElHaddad, Ahmed A.; El Tagy, Gamal; Esmat, Haytham; Shehata, Sameh; Hashim, Mohamed; Kotb, Hanan A.; Zekry, Hanan; et al.
Abstract : Biliary atresia (BA) is the most common indication for pediatric liver transplantation. We describe The BA variant: Kotb disease. Liver tissue in the Kotb disease BA is massively damaged by congenital aflatoxicosis resulting in inflammation, adhesions, fibrosis, bile duct proliferation, scarring, cholestasis, focal syncytial giant cell transformation, and typical immune response involving infiltration by CD4+, CD8+, CD68+, CD14+, neutrophil infiltration, neutrophil elastase spill, heavy loads of aflatoxin B1, accelerated cirrhosis, disruption of p53 and GSTPi, and have null glutathione S transferase M1 (GSTM1). All their mothers are heterozygous for GSTM1. This inability to detoxify aflatoxicosis results in progressive inflammatory adhesions and obliterative cholangiopathy early in life. The typical disruption of both p53 and GSTPi causes loss of fidelity of hepatic regeneration. Hence, regeneration in Kotb disease BA typically promotes accelerated cirrhosis. The immune response in Kotb disease BA is for damage control and initiation of regeneration, yet, this friendly fire incurs massive structural collateral damage. The Kotb disease BA is about actual ongoing hepatic entrapment of aflatoxins with lack of ability of safe disposal due to child detoxification-genomics disarray. The Kotb disease BA is a product of the interaction of persistent congenital aflatoxicosis, genetic lack of GSTM1 detoxification, ontogenically impaired activity of other hepatic detoxification, massive neutrophil-elastase, immune-induced damage, and disturbed regeneration. Ante-natal and neonatal screening for aflatoxicosis, avoiding cord milking, and stringent control of aflatoxicosis content of human, poultry and live-stock feeds might prove effective for prevention, prompt diagnosis and management based on our recent understanding of its patho-genomics.